Acceptance and Commitment Therapy and Weight-Related Difficulties in Overweight and Obese Adults : A Systematic Review - Patricia Pawa, Pitil; Siti Raudzah, Ghazali (SAGE Publications, 2022)
Multiple studies have investigated the efficacy of acceptance and commitment therapy (ACT) in improving psychological flexibility among overweight and obese individuals. However, to date, no specific reviews have focused on ACT and weight-related difficulties in this population. This systematic review of the literature aims to identify and assemble all ACT interventions in randomized controlled trials (RCT) that address weight-related difficulties in the treatment of overweight and obese adults. The PRISMA 2020 framework was used for the systematic review, includes manual and computerized database searches. Five databases (Medline, PubMed, Scopus, PsycInfo, and Google) were utilized to gather all articles that: (a) published in English; (b) adopted the RCT design; (c) used ACT as an intervention; (d) included adult participants aged over 18 years with BMI of over 25 kg/m2 , and (e) included weight-related difficulties and weight as outcome measures. The review identified seven studies comprising 698 overweight or obese participants of both genders. Improvements were reported in weight-related difficulties and percentage of weight loss in the ACT group and the nonACT group. The present review supports ACT as an effective intervention that can help adults with weight-related difficulties and excess body weight. Further studies should be conducted in various overweight or obese populations with a more systematic RCT research design to establish the effectiveness of ACT in this area.